Motivating Language Theory Effective Leader Talk in the Workplace - Mayfield, Jacqueline (Springer International Publishing, 2018)
This book presents the findings, applications, and theoretical underpinnings of a unique leadership communication model: motivating language theory. Drawing from management, social science, and communication theories, motivating language theory demonstrates how leader-to-follower speech improves employee and organizational well-being and drives positive workplace outcomes (such as employee performance, retention, and job satisfaction) in a wide array of settings. It presents an integrated model based on empirical findings and theoretical developments from the past three decades to explore the three dimensions of motivating language: direction giving language, empathetic language, and meaning-making language. It will be a comprehensive source for its empirical relationships, generalizability, theoretical basis, and future directions for research and practice. .